Evaluating the college of Education Program in Iraq-Baghdad and Italy-Florence in terms of ESL and TESOL Standards - Bushra Alnoori (Firenze University Press, 2018)
This study is an attempt to evaluate the College of Education Programs in Baghdad (Iraq) and the Department of Sciences of Education and Psychology in Florence (Italy) in terms of ESL (English as a Second Language) and TESOL (Teaching English to Speakers of Other Languages) standards. The program emphasizes the need for improvement in TEPs (Teacher Education Programs), which are generally not given due attention. Teacher education programs need to cover a wide range of related aspects and prepare future teachers to handle the challenges in teaching in the 21st century. The issues related to TEPs are studied by the researcher from various perspectives and the performance in both the countries namely Italy and Baghdad seem to be satisfactory on the whole. The results are better than one or the other in the different domains. Useful suggestions and recommendations are added by the researcher at the end which pave the way for future studies.   La valutazione dei percorsi di formazione in Iraq (Bagdad) e Italia (Firenze) in riferimento ai programmi ESL e TESOL Il presente articolo si propone di fornire elementi di valutazione dei programmi del Dipartimento di Scienze dell'Educazione a Bagdad (Iraq) e del Dipartimento di Scienze della Formazione e Psicologia a Firenze (Italia) in termini di standard ESL (Inglese come seconda lingua) e TESOL (programmi di insegnamento della lingua inglese ad adulti di lingua diversa dall'inglese). Tali programmi sottolineano la necessità di migliorare i percorsi di Educazione degli Insegnanti (TEP), che in genere non ricevono la attenzione necessaria. I programmi di formazione degli insegnanti è utile che ricoprano una ampia varietà di aspetti e tematiche e che li preparino ad affrontare le sfide dell'insegnamento del ventunesimo secolo. Le questioni relative ai TEP sono studiate dalla ricercatrice da diverse prospettive. Le performance al riguardo sembrano, nel complesso, essere di qualità soddisfacente in entrambi i contesti (Firenze-Italia e Baghdad-Iraq). I risultati sono migliori nell'uno o nell'altro Paese, a seconda degli ambiti in esame. Il contributo si conclude offrendo suggerimenti e raccomandazioni utili per nuove piste di ricerca.